Preparation method of magnesium alloy surface super-hydrophobic coating
By combining nanosecond laser etching and epoxy resin/stearic acid double coating system, a zigzag/unshaped structure was constructed on the surface of the magnesium alloy, which solved the problems of insufficient wear resistance, corrosion resistance and icing resistance of the magnesium alloy surface, and achieved efficient preparation and good performance of the superhydrophobic coating.
Patent Information
- Application Number
- CN202510720680.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-30
- Publication Date
- 2025-09-12
AI Technical Summary
The existing super-hydrophobic coating technology for magnesium alloy surfaces has insufficient wear resistance, corrosion resistance, anti-icing and self-cleaning performance, and the traditional preparation method has problems of environmental pollution and high cost.
Nanosecond laser etching is used to construct a U-shaped/zigzag-shaped micron-scale feature structure, combined with an epoxy resin/stearic acid double coating system, and through the laser-induced in-situ melting recrystallization mechanism and organic-inorganic interface chemical bonding, a close bond between the superhydrophobic functional layer and the substrate is achieved.
The wear resistance, corrosion resistance and anti-icing properties of the magnesium alloy surface are improved, while maintaining good self-cleaning properties, achieving the stability and durability of the superhydrophobic coating.
Smart Images

Figure CN120618822A_ABST
Abstract
Description
Technical Field
[0001] The invention discloses a method for preparing a super-hydrophobic coating, in particular a method for preparing a super-hydrophobic coating on a magnesium alloy surface, and belongs to the technical field of metal surface functional coatings. Background Art
[0002] Magnesium alloys, due to their low density, excellent vibration absorption, electromagnetic shielding, and machinability, are promising green engineering metal materials with widespread applications in the automotive, aerospace, computer, and electronics industries. With the demand for lightweight equipment and the need for energy conservation and emission reduction in industries such as marine engineering and chemical equipment, the use of magnesium alloys with high specific strength has become a trend in certain sectors. Currently, magnesium alloys exhibit broad application potential in multiple fields, but their shortcomings in wear resistance, corrosion resistance, anti-icing properties, and self-cleaning properties have limited their further application, leading to numerous targeted studies. Notably, existing modification systems often utilize fluoride or heavy metal components, potentially conflicting with the concept of green manufacturing. Against this backdrop, the development of multifunctional, integrated superhydrophobic coatings has become an important research direction. By constructing micro-nano hierarchical structures and low-surface-energy modifications, these technologies can simultaneously achieve synergistic effects such as interfacial corrosion inhibition, droplet bouncing anti-icing, and contaminant self-cleaning. These technologies, independent of external energy supply, offer a more universal solution for magnesium alloy surface engineering.
[0003] The preparation methods of superhydrophobic coatings have shown diversified development in recent years, but different technical routes have significant limitations. Chemical etching method constructs surface micro-nanostructures through acid / alkali solution corrosion (such as HNO3 or NaOH system). Although it has the advantage of low process cost, its highly corrosive reagents are prone to environmental pollution, and the reaction kinetics are difficult to accurately control, resulting in poor surface morphology uniformity. Although electrochemical deposition method (such as metal oxide / polymer co-deposition) can achieve controllable growth of submicron-level structures, the sensitivity of process parameters (potential electrolyte composition, etc.) leads to limited repeatability, and the use of precious metal electrodes (Pt / IrO2) significantly increases the scale cost. Although the sol-gel method (such as SiO2 / TiO2-based coating) has outstanding flexibility in chemical composition design, its thermal curing process (>300℃) easily induces grain boundary oxidation of the magnesium matrix, and the interface bonding strength between the coating and the substrate is insufficient, resulting in deterioration of mechanical durability. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to overcome the defects of the prior art and provide a method for preparing a super-hydrophobic coating on a magnesium alloy surface with good wear resistance, corrosion resistance, self-cleaning and anti-icing properties.
[0005] In order to solve the above technical problems, the present invention provides a method for preparing a super-hydrophobic coating on a magnesium alloy surface, comprising the following steps:
[0006] S1. The surface of the magnesium alloy substrate is smoothed and then purified;
[0007] S2. performing structured laser etching on the magnesium alloy surface after treatment in S1;
[0008] S3. After laser etching in S2, the magnesium alloy was immersed in a mixed solution of anhydrous ethanol and epoxy resin, and then taken out and dried and cooled naturally;
[0009] S4. Place the magnesium alloy prepared in S3 into a stearic acid mixed solution for modification, then take it out, dry it, and cool it naturally.
[0010] The present invention further comprises the step of mixing anhydrous ethanol (wt=99%) with epoxy resin, and then sealing the mixture in a heated magnetic stirrer at 40-50° C. and stirring for 30-40 minutes.
[0011] In the present invention, the stearic acid mixed solution is composed of anhydrous ethanol, stearic acid, and a curing agent, and the mass fractions of anhydrous ethanol, stearic acid, and curing agent are 3:1:0.05 respectively; or the stearic acid mixed solution is composed of anhydrous ethanol and stearic acid, and the mass fractions of anhydrous ethanol and stearic acid are 3:1 respectively.
[0012] The present invention further comprises the step of sealing the stearic acid mixed solution in a heated magnetic stirrer and stirring at 26-40° C. for 20-25 minutes.
[0013] In the present invention, the soaking process is soaking in an environment of 50-60° C. for 45-60 minutes.
[0014] In the present invention, the modification process is to soak in an environment of 50-60° C. for 45-60 minutes.
[0015] In the present invention, the polishing process in S1 is: using 500#, 800#, 1500# and 3000# silicon carbide sandpaper to perform step-by-step grinding in sequence.
[0016] In the present invention, the purification process in S1 is: ultrasonically vibrating in an analytical pure ethanol medium for at least 20 minutes, then drying at a constant temperature of 60° C. for 30 minutes, and finally placing the treated magnesium alloy substrate in a nitrogen protection bag.
[0017] In the present invention, the S2 laser etching process is as follows: using a fiber nanosecond laser marking machine, setting the laser scanning power to 28.5W, the scanning speed to 200mm / s, the scanning frequency to 30KHZ, and the scanning line spacing to 50-150μm.
[0018] In the present invention, the scanning path of the optical fiber nanosecond laser marking machine is in a U-shape and / or a zigzag shape.
[0019] The beneficial effects of the present invention are: (1) a U-shaped / zigzag micron-scale characteristic structure is precisely constructed on the surface of the magnesium alloy through nanosecond laser parametric processing, and then an epoxy resin / stearic acid double coating system is used to achieve nanoscale modification and low surface energy modification. It realizes a close combination of the super-hydrophobic functional layer and the substrate through the laser-induced in-situ melting recrystallization mechanism and organic-inorganic interface chemical bonding (CO-Mg bonding), which can effectively ensure the wear resistance and corrosion resistance of the magnesium alloy surface and maintain good self-cleaning and anti-icing properties; (2) the scanning path of the fiber optic nanosecond laser marking machine is U-shaped and / or zigzag, which can further improve the super-hydrophobic coating's delayed icing, anti-friction, peel strength, corrosion resistance and self-cleaning properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In the drawings, which are not necessarily drawn to scale, the same reference numerals may describe similar components in different views. The same reference numerals with letter suffixes or different letter suffixes may represent different instances of similar components. The accompanying drawings generally illustrate various embodiments by way of example and not limitation, and together with the description and claims, serve to illustrate the claimed embodiments. Where appropriate, the same reference numerals are used throughout the drawings to refer to the same or similar parts. Such embodiments are illustrative and are not intended to be exhaustive or exclusive of the present apparatus or method.
[0021] Figure 1 SEM images of super-hydrophobic coating samples according to embodiments of the present application are shown, a and b are SEM images of different areas in the zigzag pattern, c is a SEM image of the center area of the zigzag pattern, and d is a SEM image of the edge area of the zigzag pattern;
[0022] Figure 2 Figure 1 shows the 3D images and contour lines of the super-hydrophobic coating sample according to an embodiment of the present application, where ab is the actual measurement image obtained by 3D scanning, cd is the 3D image of the zigzag shape and the zigzag shape, and ef is the contour line of the zigzag shape and the zigzag shape;
[0023] Figure 3 The EDS scanning element distribution diagram of the surface of the super-hydrophobic coating sample according to the embodiment of the present application is shown;
[0024] Figure 4 The contact angle and sliding angle diagrams of the superhydrophobic coating samples according to the embodiments of the present application are shown, where ab is the highest static contact angle of the zigzag and zigzag shapes, and cd is the contact angle (CA) and sliding angle (SA) of the zigzag and zigzag shapes;
[0025] Figure 5Figures 1 and 2 show friction and wear test results of super-hydrophobic coating samples according to embodiments of the present application, where ab is a schematic diagram of friction with a zigzag pattern perpendicular to and parallel to the texture direction, cd is a schematic diagram of friction with a zigzag pattern perpendicular to and parallel to the texture direction, e is the contact angle (CA) of the surface after different wear cycles with a zigzag pattern, and f is the contact angle (CA) of the surface after different wear cycles with a zigzag pattern;
[0026] Figure 6 Figures showing electrochemical experiments of superhydrophobic coating samples according to embodiments of the present invention. a is the Nyquist plot of different samples in 3.5 wt% NaCl solution, b is the impedance modulus plot, c is the electrochemical polarization curve, d is the electrochemical working circuit, and e is a schematic diagram of electrochemical corrosion.
[0027] Figure 7 Figures show anti-icing experiments on superhydrophobic coating samples according to embodiments of the present invention. Figures ac show the freezing process of a zigzag pattern with widths of 50 μm, 70 μm, and 90 μm; df shows the freezing process of a zigzag pattern with widths of 50 μm, 70 μm, and 90 μm; g shows the freezing process of an untreated surface; and h is a schematic diagram of the ice-delay principle.
[0028] Figure 8 Figures showing ice peeling experiments on super-hydrophobic coating samples according to embodiments of the present invention. a shows the anti-icing adhesion strength of a zigzag sample, a zigzag sample, and their respective etched samples; b shows the static contact angle and rolling angle after different icing cycles (zigzag, 70 μm scanning spacing); c shows the static contact angle and rolling angle after different icing cycles (zigzag, 70 μm scanning spacing).
[0029] Figure 9 Figures showing the self-cleaning experiments of super-hydrophobic coating samples according to embodiments of the present invention are shown. a) shows the self-cleaning effect of an untreated surface, b) shows the self-cleaning effect of a zigzag pattern, and c) shows the self-cleaning effect of a zigzag pattern. DETAILED DESCRIPTION
[0030] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings herein can be arranged and designed in various different configurations.
[0031] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention as claimed, but rather merely represents selected embodiments of the present invention. All other embodiments derived by persons of ordinary skill in the art based on the embodiments of the present invention without creative effort are intended to fall within the scope of protection of the present invention.
[0032] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, it does not need to be further defined or explained in subsequent drawings.
[0033] The following embodiments of the present invention are described in detail with reference to the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments may be combined with each other.
[0034] Example 1
[0035] Step 1: Selection and processing of substrate:
[0036] In this embodiment, Mg-3Al-1Zn (AZ31) magnesium alloy that complies with the GB / T5153-2002 standard is selected as the base material and processed into a regular sample of 20 mm×20 mm×5 mm by a precision wire cutting device.
[0037] In order to construct the micro-nano hierarchical structure required for the super-hydrophobic surface, the sample surface was pretreated using a gradient grinding process: 500#, 800#, 1500# and 3000# silicon carbide sandpaper were used for step-by-step grinding until a mirror-level surface finish was obtained.
[0038] Subsequently, a KQ-50DB CNC ultrasonic cleaner was used for a two-stage purification treatment: first, ultrasonic vibration was performed in an analytical pure ethanol medium for 20 minutes to remove surface adsorbed particles, and then the samples were dried at a constant temperature of 60°C in a DHG-9030A blast drying oven for 30 minutes. Finally, the pretreated samples were placed in a nitrogen protection bag for use.
[0039] Step 2: Laser etching:
[0040] Laser etching technology can efficiently construct hierarchical micro-nanostructures through the interaction between femtosecond / nanosecond lasers and the surface of magnesium alloys. Its core advantages are reflected in the following three aspects: (1) Precise morphology adjustability: Based on the coordinated control of laser power (10-100W), scanning speed (0.1-5mm / s) and spot overlap rate (30-70%), it can accurately design multi-scale composite structures ranging from nanoscale ripples (<200nm) to micron-scale pits (1-20μm), achieving directional optimization of surface wettability and mechanical properties; (2) Process environmental friendliness: No aqueous / organic chemical reagents are involved in the entire process, avoiding the pollution risks of traditional chemical etching or electroplating processes, and meeting the needs of sustainable development; (3) Matrix bonding strengthening: The laser-induced melting-resolidification process enables the micro-nanostructure to form a metallurgical bond with the magnesium alloy substrate, significantly improving the interface bonding strength (up to 2-3 times that of traditional coatings), and avoiding the interface peeling problem caused by mechanical stress in the multi-layer coating system.
[0041] In step 2, the magnesium alloy sample processed in step 1 is placed on a laser processing platform and structurally etched using a fiber nanosecond laser marking machine (the FMF30W intelligent fiber laser marking machine is used in this embodiment).
[0042] The FMF30W intelligent fiber laser marking machine was set to a zigzag scanning path with a laser scanning power of 28.5W, a scanning speed of 200mm / s, a scanning frequency of 30kHz, and a scanning line spacing of 70μm. After the laser etching, the sample was immediately sealed in a sample bag for future use to prevent oxidation of the magnesium alloy and affect subsequent preparation.
[0043] Step 3: Preparation of super hydrophobic coating:
[0044] After mixing anhydrous ethanol (99% by weight) and epoxy resin in a beaker, seal the beaker with plastic wrap and place it in an LCD digitally controlled heated magnetic stirrer (model MS-H-Pro+) for 30 minutes at 40°C. The magnesium alloy sample etched in step 2 was then placed in the mixture and immersed in a constant temperature water bath (model DXY-6) at 60°C for 1 hour. The sample was then removed from the mixture and placed in a forced air drying oven, dried at 70°C for 6 hours, and then cooled to room temperature. In this example, 30 ml of anhydrous ethanol and 0.3 g of epoxy resin glue were mixed.
[0045] Anhydrous ethanol, stearic acid, and a curing agent were mixed in a mass fraction of 3:1:0.05 to prepare a stearic acid mixed solution. The solution was then sealed in a beaker with plastic wrap and placed in an LCD digitally controlled heating magnetic stirrer (model MS-H-Pro+) for 20 minutes at 40°C. The magnesium alloy sample, after cooling, was then placed in a constant temperature water bath (model DXY-6) at 60°C for 1 hour. The sample was then removed from the oven and dried at 90°C for 8 hours before being cooled to room temperature to obtain a superhydrophobic coating on the magnesium alloy surface.
[0046] Example 2
[0047] Step 1: selection and processing of substrate, same as in Example 1.
[0048] Step 2: laser etching, same as in Example 1.
[0049] Step 3: Preparation of super hydrophobic coating:
[0050] After mixing anhydrous ethanol (99% by weight) and epoxy resin in a beaker, seal the beaker with plastic wrap and place it in an LCD digitally controlled heated magnetic stirrer (model MS-H-Pro+) for 40 minutes at 50°C. The magnesium alloy sample, etched in step 2, was then placed in the mixture and immersed in a constant temperature water bath (model DXY-6) at 50°C for 45 minutes. The sample was then removed and placed in a forced air drying oven, dried at 60°C for 5 hours, and then cooled to room temperature. In this example, 30 ml of anhydrous ethanol and 0.3 g of epoxy resin glue were mixed.
[0051] Anhydrous ethanol, stearic acid, and a curing agent were mixed in a mass fraction of 3:1:0.05 to prepare a stearic acid mixed solution. The solution was then sealed in a beaker with plastic wrap and placed in an LCD digitally controlled heated magnetic stirrer (model MS-H-Pro+) for stirring at 26°C for 25 minutes. The magnesium alloy sample, which had been immersed and cooled, was then placed in a constant temperature water bath at 50°C (model DXY-6) for 45 minutes. The sample was then removed from the oven and dried at 80°C for 9 hours before being cooled to room temperature to obtain a superhydrophobic coating on the magnesium alloy surface.
[0052] In other embodiments, the FMF30W intelligent fiber laser marking machine uses four pitches of 50 μm, 110 μm, 90 μm, 130 μm, and 150 μm for laser etching.
[0053] In other embodiments, anhydrous ethanol and stearic acid are mixed in a mass fraction of 3:1 to prepare a stearic acid mixed solution.
[0054] In order to systematically characterize the surface properties of the superhydrophobic layer, a variety of characterization methods are used to comprehensively analyze the superhydrophobic coating on the surface of the magnesium alloy prepared in Examples 1 and 2. The research system reveals the regulation rules of the laser trajectory on the static and dynamic wetting behaviors of the samples, tests the various properties of the samples at 70μm, and makes a quantitative study on the self-cleaning performance characterization.
[0055] First, a Hitachi High-Tech scanning electron microscope (SU3500 Hitachi High-Tech Corporation) was used to observe the microstructure of the samples. The operating conditions were an accelerating voltage of 15 kV and a working distance of 8 mm. Figure 1 As shown, for Examples 1 and 2, the surface morphology of the samples was observed at a higher magnification with a scanning line spacing of 70 μm. a and b are SEM images of different areas in the zigzag pattern, c is the SEM image of the center area of the zigzag pattern, and d is the SEM image of the edge area of the zigzag pattern. Figure 1 It can be seen that the entire etched morphology is uniform, the line spacing is in line with expectations, and provides a structural basis. When the laser scanning spacing is 70μm, both structures show optimal wetting performance.
[0056] Subsequently, the element distribution analysis of the sample surface was performed by energy dispersive spectroscopy (EDS, Oxford Instruments X-Max 50mm), and the scanning area covered the entire field of view to obtain the distribution of surface elements. Figure 3 As shown, by comparing the surface peaks of stearic acid modified magnesium alloy ( Figure 3 a) and valley ( Figure 3 b) The EDS element distribution characteristics of the position revealed that the three core elements C, O, and Mg showed a regular spatial distribution on the surface. It is worth noting that the C and O element contents in the peak area are significantly higher than those in the valley (C peak: valley ≈ 1.3: 1, O peak: valley ≈ 1.2: 1), and their distribution trajectories show a high degree of spatial coupling in the microscopic morphology. This gradient feature of element distribution is closely related to the chemical coordination mechanism between the carboxyl group (-COOH) in the stearic acid molecule and the magnesium matrix - the surface protrusion structure has a higher specific surface area and reaction activity, which is more conducive to the dehydration condensation reaction between the carboxyl group in the stearic acid molecule and Mg (OH) 2, resulting in the enrichment of characteristic elements in the peak. This phenomenon confirms from the element distribution level that the stearic acid molecule achieves gradient surface modification through chemical bonding, and the spatial enrichment behavior of the C element in the surface micro-nanostructure provides a key material basis for constructing a stable superhydrophobic interface.
[0057] Next, an ultra-depth-of-field three-dimensional microscope (VW-9000C, Keyence Corporation) was used to analyze the three-dimensional morphology of the sample with a measurement range of (1000 μm × 1000 μm) and a resolution of 0.1 μm to obtain the microscopic morphology and roughness parameter (Sa) of the sample surface. Figure 2 As shown in the figure, the center area of the U-shaped structure has a regular periodic grid arrangement, while the edge areas have local periodic distortion. The center and edge areas of the zigzag structure have complete geometric contours, and the etching uniformity is good due to the uniform distribution of laser energy.
[0058] The contact angle and sliding angle of the superhydrophobic coatings on the magnesium alloy surfaces prepared in each example were measured using an optical contact angle meter (JC2000D2A, Shanghai Zhongchen Digital Technology Equipment Co., Ltd.) to measure the static contact angle (CA) and sliding angle (SA). Deionized water (pH 6.5±0.2) was used as the measuring solution, with a droplet volume of 10 μL. Measurements were repeated at five different locations (top, bottom, left, right, and center), and the average result was taken. Figure 4 The graphs (a, b) represent the state when the scanning line spacing is 70 μm, (b) represent the highest static contact angles for the zigzag and folded shapes, and (c) represent the contact angle (CA) and sliding angle (SA) for the zigzag and folded shapes. Through these characterization methods, the surface morphology, element distribution, and wetting properties of the superhydrophobic samples were systematically evaluated, providing detailed characterization data supporting their application in the superhydrophobic field.
[0059] Table 1 Static contact angle and sliding angle of the U-shaped specimen (test water drop volume is 10 μL)
[0060] Scan line spacing / μm Contact angle / ° Sliding angle / ° 50 154.75±0.7 5.5±0.3 70 157.65±0.5 4.4±0.4 90 154.75±0.9 5.5±0.5 110 152.50±1.1 6.2±0.3 130 152.00±0.7 6.3±0.4 150 151.75±1.3 6.6±0.4
[0061] Table 2 Static contact angle and sliding angle of zigzag specimens (test water drop volume is 10 μL)
[0062] Scan line spacing / μm Contact angle / ° Sliding angle / ° 50 156.25±1.1 5.0±0.2 70 158.25±0.3 4.1±0.3 90 153.50±0.5 5.7±0.5 110 154.00±0.7 5.6±0.3 130 154.75±0.9 5.6±0.4 150 152.25±1.0 6.4±0.5
[0063] The friction resistance test of the super-hydrophobic coating on the surface of the magnesium alloy prepared in Examples 1 and 2 was conducted as follows: a silicon carbide sandpaper of model 1000# was placed on a smooth glass plate as a friction medium. The super-hydrophobic sample was fixed on a friction device, and a 500g weight was placed on its surface to apply a quantitative pressure. Subsequently, the sample was pulled at a constant speed of 1cm / s by an external force traction device to cause relative friction with the sandpaper. The friction experiment was divided into two groups: perpendicular to the direction of the sandpaper grain (perpendicular grain group) and parallel to the direction of the sandpaper grain (along the grain group). The total test distance of each friction cycle was 20cm (including a 10cm outward stroke and a 10cm return stroke). After the friction experiment was completed, the static contact angle (CA) and sliding angle (SA) of the sample surface were measured using an optical contact angle meter. The measurement positions included five areas: the top, bottom, left, right and center of the sample to ensure the representativeness and accuracy of the measurement results. Each group of experiments was repeated three times, and the average value was taken as the final result. The measurement error was controlled within ±1°, as shown in the figure. Figure 5 shown.
[0064] from Figure 5 As can be seen from the figure, the zigzag structure exhibits superior wear resistance compared to the U-shaped structure. After nine cycles of vertical-vertical wear, the contact angle remained at 147.8±2.1°, while the U-shaped structure's contact angle decreased to 144.6±2.7° after nine cycles of the same wear. The zigzag structure exhibits greater structural stability during friction and wear due to its high unidirectional load-bearing capacity. The U-shaped structure exhibits a more pronounced decrease in contact angle after wear due to its uniform force distribution and lower local load.
[0065] Electrochemical corrosion test of the super-hydrophobic coating on the magnesium alloy surface prepared in Examples 1 and 2: The electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization curve were measured using a Garmy electrochemical workstation (Interface 1000E) in a three-electrode system. In the experiment, the super-hydrophobic sample (exposed area of 4 cm 2 ) as the working electrode, saturated calomel electrode (SCE) as the reference electrode, and platinum as the counter electrode. The frequency range of electrochemical impedance spectroscopy measurement was 10mHz to 100kHz, and the scan rate of the potentiodynamic polarization curve was set to 1mV / s. All experiments were carried out in a 3.5wt% NaCl aqueous solution to simulate the corrosion conditions in actual application environments. Figure 6 It can be seen that the zigzag coating has better corrosion resistance than the rounded one. The corrosion resistance of the zigzag coating is significantly improved, and the self-corrosion current is reduced from 7.80×10-5A / cm2 to 2.46×10-5A / cm 2 ; Its charge transfer resistance is 267.84 times that of the untreated substrate.
[0066] The anti-icing performance test of the super-hydrophobic coating on the surface of the magnesium alloy prepared in each embodiment was as follows: 0.04 mL of deionized water was dropped on the center of the magnesium alloy sample, which was placed horizontally on the anti-icing test bench. The temperature was set to -20°C, and the surface state of the water drop was observed every 200 seconds until the water drop was completely solidified. The ice adhesion strength was then measured by dropping 0.04 mL of water droplets on the surface of the 15 mm × 15 mm sample. After the water sample was completely frozen, a horizontal force was applied and measured, and the maximum force used to push down the ice was recorded. Figure 7 As shown in the figure, a, c, e are the freezing processes of the U-shaped sample with line spacing of 50μm, 70μm and 90μm respectively, b, d, f are the freezing processes of the zigzag sample with line spacing of 50μm, 70μm and 90μm respectively, g is the freezing process of the untreated surface, and h is a schematic diagram of the ice delay principle. Figure 7 It can be seen that compared with the untreated surface solidification time of 15s, the super-hydrophobic coating on the magnesium alloy surface prepared in the embodiment of the present invention has a significant effect of delaying freezing, among which the U-shaped solidification time is as high as 731s and the zigzag solidification time is 621s, and its anti-freeze effect is obvious.
[0067] like Figure 8 As shown in the figure, a is the anti-icing adhesion strength of the zigzag, zigzag, and untreated samples, b is the static contact angle and sliding angle after different icing cycles (zigzag, scanning spacing 70μm), and c is the static contact angle and rolling angle after different icing cycles (zigzag, scanning spacing 70μm). From the comparison of ice peeling strength performance, the zigzag structure performs better and is more resistant to multiple peeling: the ice adhesion strength is significantly lower (49.63kPa for the zigzag vs. 66.67kPa for the zigzag), and the zigzag structure is more resistant to multiple peeling (it still remains superhydrophobic after 5 peelings).
[0068] The self-cleaning performance test of the super-hydrophobic coating on the surface of the magnesium alloy prepared in Examples 1 and 2 was as follows: the slope was set to 10° and 0.4g of 34# high-purity quartz sand was evenly sprinkled on the surface of the sample at a flow rate of 0.5mL / s. The sample was flushed at a height of 30cm from the surface of the sample, and the mass of the quartz sand flushed for the same time was measured. Figure 9Shown in the figure, a is an untreated surface self-cleaning effect diagram and schematic diagram, b is a zigzag self-cleaning effect diagram and schematic diagram c is a zigzag self-cleaning effect diagram and schematic diagram. Compared to untreated surface, the self-cleaning efficiency of embodiment 1 and 2 super-hydrophobic surface coating is improved by an average of 4 times, wherein the zigzag structure is due to a more excellent micro-nano composite structure, and completes self-cleaning faster than zigzag (1.4 seconds vs 2 seconds), with higher efficiency (99.2% vs 98.5%). In the present invention, micron-sized nipples are formed on the surface of the magnesium alloy by laser etching (referring to the micron-sized protrusions formed on the surface, their size is generally between a few microns to tens of microns), and micron-sized nipples can increase the roughness of the surface, thereby providing a larger surface area, which is very effective for enhancing hydrophobicity and ice-phobicity. Stearic acid is deposited onto the rough structure laser-etched onto the magnesium alloy surface to form fine particles - wax crystals, which can be coated on the surface of micron-sized papillae or embedded in the gaps between papillae; the low surface energy of wax crystals helps to reduce the contact angle between the droplet and the surface, thereby providing superhydrophobicity.
[0069] The above description is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements can be made without departing from the principles of the present invention. These improvements should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a super-hydrophobic coating on a magnesium alloy surface, characterized in that: The following steps are involved: S1. The surface of the magnesium alloy substrate is smoothed and then purified; S2. performing structured laser etching on the magnesium alloy surface after treatment in S1; S3. After laser etching in S2, the magnesium alloy was immersed in a mixed solution of anhydrous ethanol and epoxy resin, and then taken out and dried and cooled naturally; S4. Place the magnesium alloy prepared in S3 into a stearic acid mixed solution for modification, then take it out, dry it, and cool it naturally.
2. The method for preparing a super-hydrophobic coating on a magnesium alloy surface according to claim 1, wherein The method further comprises the steps of mixing anhydrous ethanol and epoxy resin, and then sealing the mixture in a heated magnetic stirrer and stirring the mixture at 40-50° C. for 30-40 minutes.
3. The method for preparing a super-hydrophobic coating on a magnesium alloy surface according to claim 1 or 2, wherein: The stearic acid mixed solution consists of anhydrous ethanol, stearic acid, and a curing agent, and the mass fractions of anhydrous ethanol, stearic acid, and curing agent are 3:1:0.05 respectively; or the stearic acid mixed solution consists of anhydrous ethanol and stearic acid, and the mass fractions of anhydrous ethanol and stearic acid are 3:1 respectively.
4. The method for preparing a super-hydrophobic coating on a magnesium alloy surface according to claim 3, wherein: The method further comprises the step of sealing the stearic acid mixed solution in a heated magnetic stirrer and stirring the mixture at 26-40° C. for 20-25 minutes.
5. The method for preparing a super-hydrophobic coating on a magnesium alloy surface according to claim 3, wherein: The soaking process is to soak in an environment of 50-60° C. for 45-60 minutes.
6. The method for preparing a super-hydrophobic coating on a magnesium alloy surface according to claim 3, wherein: The modification process is to soak in a 50-60° C. environment for 45-60 minutes.
7. The method for preparing a super-hydrophobic coating on a magnesium alloy surface according to claim 1, wherein: The polishing process in S1 is: using 500#, 800#, 1500# and 3000# silicon carbide sandpaper to perform step-by-step grinding in sequence.
8. The method for preparing a super-hydrophobic coating on a magnesium alloy surface according to claim 1, wherein: The purification process in S1 is as follows: ultrasonically vibrating in an analytical pure ethanol medium for at least 20 minutes, then drying at a constant temperature of 60° C. for 30 minutes, and finally placing the treated magnesium alloy substrate in a nitrogen protection bag.
9. The method for preparing a super-hydrophobic coating on a magnesium alloy surface according to claim 1, wherein: The S2 laser etching process is as follows: using a fiber nanosecond laser marking machine, setting the laser scanning power to 28.5W, the scanning speed to 200mm / s, the scanning frequency to 30KHZ, and the scanning line spacing to 50-150μm.
10. The method for preparing a super-hydrophobic coating on a magnesium alloy surface according to claim 1, wherein: The scanning path of the optical fiber nanosecond laser marking machine is in a U-shaped and / or zigzag shape.
Citation Information
Cited By
Silane coupling agent reinforced wear-resistant super-hydrophobic coating and preparation method thereof
CN121895857A